The Impact of Solvency Risk and Asset Quality Risk on the Asset Size of Commercial Banks (An Applied Study on Samples of Commercial Banks Registered on the Iraqi Stock Exchange 2011-2020) (Global Journal of Management and Business Research, 2024)
Assets are economic resources owned by a bank, in the form of tangible or intangible properties that are suitable for repaying debts. In other words, assets are those that can be easily converted into cash within a specific time period. Bank assets must be hedged against numerous risks. This study aims to investigate the impact of solvency risks and asset quality risks on the assets of commercial banks by measuring and analyzing the identified study variables. This study addresses the problem of asset loss in commercial banks, whether fixed or liquid, and offers solutions towards attracting prospective investors and retaining current ones via asset preservation and increment. Researchers can also benefit from this study in terms of variable measurements and key concept identification. The study samples entailed the Commercial Bank of Iraq (BCOI) and the National Investment Bank (BNOI) over the study period from 2011 to 2020.
Keywords: risk solvency; asset quality risk; and commercial banks